Joint university-industry laboratories through the lens of proximity dimensions: moving beyond geographical proximity. Issue 4 (25th November 2020) - Mahdad, Maral; Minh, Thai Thi; Bogers, Marcel L.A.M.; Piccaluga, Andrea
Abstract : Purpose: There is little known about investigating the importance of all proximity dimensions simultaneously as a result of geographical proximity on university-industry collaborative innovation. This paper aims to answer the question of how geographically proximate university and industry influence cognitive, social, organizational, institutional and cultural proximity within university-industry joint laboratories and finally, what is the outcome of these interplays on collaborative innovation. Design/methodology/approach: The study uses an exploratory multiple-case study approach. The results are derived from 53 in-depth, semistructured interviews with laboratory directors and representatives from both the company and the university within 8 joint laboratories of Telecom Italia (TIM). The data collection was carried out in 2014 and 2015. The analysis follows a multi-grounded theory approach and relies on a mix of deductive and inductive reasoning with the final goal of theoretical elaboration. Findings: This study finds the role of social and cultural proximity at the individual level as a result of geographical proximity as an enabler of collaborative innovation by triggering mutual learning, trust formation and frequent interactions. Cognitive proximity at the interface level could systematically influence collaborative innovation, while organizational and institutional proximity has marginal roles in facilitating collaborative innovation. The qualitative analysis offers a conceptual framework for proximity dimensions and collaborative innovation within university-industry joint laboratories. Practical implications: The framework not only advances state-of-the-art university-industry collaboration and proximity dimension but also offers guidance for managers in designing collaborative innovation settings between university and industry. Originality/value: With this study, the paper advances the understanding beyond solely the relationship between proximity and collaboration and shed light on the interplay between geographical proximity and other proximity dimensions in this context, which has received limited scholarly attention.